Fatalities Due to Poisoning with Aluminum Phosphide (Rice Pill) and Methadone - Astaraki, Peyman; Ahadi, Maryam; Salehinejad, Foroutan; Honardoost, Vahideh (Drug Research, 2021)
Acute poisoning is commonly seen with pharmaceutical substance or pesticides. Understanding pattern of acute poisoning due to different agents can enable better emergency management. The aim of this study is to present and evaluate the fatality-related data of acute poisoning due to aluminum phosphide (rice pills) and methadone. This descriptive-analytical study was performed on patients Shahid Rahimi Hospital due to poisoning with rice tablets (aluminum phosphide) and methadone from 2015–2020. The data collection tool was a questionnaire using with demographic data, type and dose of poison and clinical presentation, duration of hospitalization was obtained and statistically analyzed. Out of 19 238 patients with poisoning referred to this center, 412 people referred to the hospital due to rice pill poisoning, of which 56 (13.59%) died and among 2157 patients due to methadone poisoning, 22 of them (1.09%) died. In both the groups, rice pill and methadone, there were more male patients 53.57 and 81.81%, respectively. In aluminum phosphide poisoning, the greatest population was in the age group (15–35). However, no specific age group was seen in methadone poisoning. The duration of hospitalization and the time of referral to the emergency department to the death of the patient was significantly correlated with mortality in both the groups. The prevalence of intentional rice kill poising was greatest, effecting young population, we recommend that health care awareness program and training should be provided in this regard. Furthermore, psychiatric care should be made easily available in the region.
Keywords: poisoning; aluminum phosphide; rice pills; methadone; pesticides; pharmaceutical